The Effect of Apple (Malus sylvestris mill) as a Natural Ingredient to Prevent Hair Loss - Chintya Redina Habsari; Merry Indah Sari; Yulisna (Medula, 2019)
Hair serves to protect the skin from bad influences, such as eyebrows that protect and prevent sweat that will flow to the eyes. While the nose hair functions as filtering the dust on the nose. Hair also has a role in protection against; adverse environment, including cold or hot temperatures, and ultraviolet light. Hair is not uncommon as confidence. Hair loss to cause baldness is a problem that is enough to worry about high self when they interact. Hair loss can be caused by many factors that are organized into endogenous: due to systemic disease, hormonal, nutritional status, intoxication, or a genetic disorder and exogenous factor in the form of stimulus from the environment and hair cosmetics. Today there are many studies of natural plants or herbal ingredients that can be used to treat hair loss. One of the plants that can grow hair is apple. Apples contain procyanin B-2 naturally found in apples. Apple extract is then made for hair tonic or cream proven to accelerate hair growth.